Shear test characterization of 3d printed polyamide reinforced carbon fiber composites - Nisa Naima Khalid; Fatin Zahidah Awang Adi; Nabilah Afiqah Mohd Radzuan; Abu Bakar Sulong (Penerbit Universiti Kebangsaan Malaysia, 2023)
The issue of delamination occurring on PACF materials is a structural application failure due to poor mechanical strength. The bonding process of composite materials between layers using fused deposition modeling (FDM) printing affects the tensile strength of the material. The main objective of this study was to study the shear strength of polyamide reinforced carbon composite (PACF) materials by using shear test method and to study the effect of fractured or delamination surfaces during shear testing. In this study, PACF material was printed using FDM technique through Ultimate S3 machine. A total of 20 printed PACF specimens underwent a semi-overlapping adhesion process using Loctite E-20HP epoxy adhesive which required curing for 24 hours at room temperature. Shear test methods were performed on PACF composite specimens using Universal Testing Machine. Furthermore, PACF samples were conducted experiments to determine the physical properties of the composites of the material as well as Scanning Electron Microscopy (SEM) experiments through fractured or eliminated surfaces. Based on the results obtained, the PACF material has a high shear tensile strength compared to that of epoxy adhesives with an average rate of 1.6 MPa respectively. This is may due to the low curing temperature and the thick epoxy layer. It was observed that the FDM printing method produces a porous print layer that can facilitate delamination to occur.